2015
DOI: 10.7314/apjcp.2015.16.8.3313
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Perceived Social Support among Caregivers of Patients with Cancer

Abstract: The purpose of this study is to describe the relationship between caregiver burden and perceived social support among caregivers of patients with cancer. The research was conducted in a university hospital in İzmir, Turkey. Eighty patient relatives who provided care service to patients with cancer who were admitted at hematology and oncology clinics participated in the study. The findings indicated that the care burden score was mild level. The mean of the perceived social support score was 58.4±21.0 supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 19 publications
5
34
1
4
Order By: Relevance
“…However, the associations of support from family and friends with caregiver burden are under-researched. The literature has consistently shown that support from friends was a protective factor, on the basis of the few studies reporting support from family and friends in caregivers of patients with cancer and stroke [28][29][30]. By contrast, the results for support from family were mixed: two studies reported a non-significant correlation with caregiver burden and one study found that support from family was also a protective factor [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the associations of support from family and friends with caregiver burden are under-researched. The literature has consistently shown that support from friends was a protective factor, on the basis of the few studies reporting support from family and friends in caregivers of patients with cancer and stroke [28][29][30]. By contrast, the results for support from family were mixed: two studies reported a non-significant correlation with caregiver burden and one study found that support from family was also a protective factor [28].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of social support was also important and may indicate the amount of hands‐on care that caregivers themselves provide to patients as well as opportunities for respite from caregiving. This has not been identified as a contributing factor in prior studies of caregiving in older adults with cancer, but has been noted in other studies of caregivers of cancer and noncancer patients . Poor caregiver mental health is associated with caregiver QOL, potentially suggesting that a caregiver's coping strategies and outlook on life are important to his/her QOL .…”
Section: Discussionmentioning
confidence: 89%
“…Selanjutnya apabila tekanan dan beban keluarga lantaran daripada ketidakcekapan mereka menjalankan penjagaan menjadikan efikasi kendiri dan penghargaan kendiri yang keluarga tersebut milikki menjadi rendah (Carlander, Sahlberg-Blom, Hellstrom & Ternestedt, 2011;Kim, Baker, & Spillers, 2007). Kajian literatur menunjukkan bahawa pengalaman keluarga dalam penjagaan pesakit kanser dapat dikategorikan kepada empat aspek iaitu beban dalam penjagaan (Kahriman & Zaybak, 2014;Rha, Park, Song, Lee, & Lee, 2015), efikasi kendiri (Bisschop, Kriegsman, Beekman, & Deeg, 2004;Campbell et al, 2004;Kershaw et al, 2008;Yeung & Lu, 2014), tekanan (Juarez et al, 2008;Soylu, Ozaslan, Karaca, & Ozkan, 2015) dan penghargaan kendiri (Moreira, Sousa, Poveda, & Turrini, 2015).…”
Section: Pengalaman Keluarga Dalam Berhadapan Dengan Proses Penjagaanunclassified